Reshoring: impact on the U.S. economy - Wieczorek, Samantha (University of Wisconsin--Stout. Research Services, 2014)
After decades of loss in manufacturing jobs, the recent trend has revealed that some production facilities are shifting their operations back into the United States. Job growth has been the focus of recent political and policy debates. The debate has rather intensified at the aftermath of the recent financial crisis during which the official unemployment rate has reached a staggering 10% at the peak of the crisis. The objective of this paper is to analyze potential factors which have an impact on the manufacturing production index in the U.S., using data from 2000 to 2012. Such variables as productivity, educational attainment, globalization, and business cycle have been found to exert a statistically significant impact on the manufacturing production index. To gain a better understanding of the business decision of shifting production facilities, industry professionals were interviewed. The information gathered from the interviews reflects the prominent impact of technology and the level of training given to employees on business decisions to move their production facilities, a viewpoint consistent with my empirical results.
Research article with tables.
Keywords: manufacturing; reshoring; U.S.; growth; Manufacturing industries--United States; Economic development--United States